(NlO\NGRIN r(B. (NwANGNERA(B. (NpUTEWODITELI PO OPERAM I BALETAM(B.s (NmONOGRAFIQs - (Ng(B. (Nw(B. (NkRAUKLISs ((NmOSKWA s (NmUZYKAs, 1988)
(NmNOGOSTORONNQQ DEQTELXNOSTX rIHARDA wAGNERA (B(1813-1883) (NZANIMAET WYDA@]ESSQ MESTO W ISTORII MIROWOJ KULXTURY(B.s
Keywords: (NMONOGRAFIQs